Characterizing and Distinguishing 'Innovative Start-ups' Among Micro, Small and Medium Enterprises (MSME). Issue 1 (June 2020) - Krishnan, S. Navaneetha; Ganesh, L. S.; Rajendran, C.
Start-ups are entrepreneurial ventures, having a high risk of failure (Bortolini et al., 2018; Spender et al., 2017). The risk of failures of Start-ups can be minimized if they are characterized well, and the appropriate macro- and micro-level policy interventions can be introduced. Our literature review (LR) on Start-ups reveals that they are addressed by different names, namely, Hi-Tech firms, University spin-offs, Innovative Start-ups (ISs), Lean Start-ups, Silicon Valley Start-ups and New Technology-Based Firms (NTBF). (Tripathi, Seppanen et al., 2018; Silva et al., 2020; Wiesenberg et al., 2020). It is also observed that Start-ups are referred to as small business and Micro, Small and Medium Enterprises (MSMEs). A systematic literature review (SLR) of Start-ups is presented here and used as the basis for characterizing them. We propose (proposition-1) that these Start-up firms, addressed by different names, as referred above, can be grouped, characterized and identified as ISs. Based on a robust characterization of ISs, this article proposes that ISs are a subset of MSMEs. From a comparative study of ISs and MSME, we propose (proposition-2) a framework that shows MSMEs can be conceptually split into ISs and Conventional MSMEs (C-MSMEs), with an intersection between ISs and C-MSME. This study has also identified four new research areas related to Start-ups and MSMEs. The above characterization and differentiation of ISs from other entrepreneurial ventures will help policymakers, entrepreneurs, and investors to understand ISs and C-MSMEs better and develop suitable policy interventions and risk mitigation strategies.